Freeway Substances for The Vision of Upcoming Infrastructures - Sandeep Nasier (International Journal of Advanced Science and Technology, 2020)
In the approachingcenturies, freeways and vehicle infrastructure is going to face different changes due to different points like in today’s world, passengers wants comfort in every point whether it is cars seat or whether it is the temperature inside the car everything should be comfortable and in this the main role is played by the highways on which everyone is going to travel. Highways are effected by different things like weight carried by the vehicle on the highways, are the highways made according to the weather conditions in the specified area or not, population growth.